Retention of Mitochondria in Mature Human Red Blood Cells as the Result of Autophagy Impairment in Rett Syndrome - Sbardella, Diego (Sci Rep, 2017)
Rett Syndrome (RTT), which affects approximately 1:10.000 live births, is a X-linked pervasive neuro-developmental disorder which is caused, in the vast majority of cases, by a sporadic mutation in the Methyl-CpG-binding protein-2 (MeCP2) gene. This is a transcriptional activator/repressor with presumed pleiotropic activities. The broad tissue expression of MeCP2 suggests that it may be involved in several metabolic pathways, but the molecular mechanisms which provoke the onset and progression of the syndrome are largely unknown. In this paper, we report that primary fibroblasts that have been isolated from RTT patients display a defective formation of autophagosomes under conditions of nutrient starvation and that the mature Red Blood Cells of some RTT patients retain mitochondria. Moreover, we provide evidence regarding the accumulation of the p62/SQSTM1 protein and ubiquitin-aggregated structures in the cerebellum of Mecp2 knockout mouse model (Mecp2 (−/y)) during transition from the non-symptomatic to the symptomatic stage of the disease. Hence, we propose that a defective autophagy could be involved in the RTT clinical phenotype, which introduces new molecular perspectives in the pathogenesis of the syndrome.